Implementing Modern Technology for Vital Sign Monitoring to Enhance Athletic Training and Sports Performance wos:000929624700001 DOI:10.3390/su15032520 Sustainability - Enoiu Razvan Sandu (Sustainability, 2023)
1) Background: Applying medical procedures to keep track of athletes’ metabolic health is a well-known behavior for increasing sports performance. This study’s primary goal was to examine whether implementing a health-screening routine using invasive and non-invasive methods in a mountain running training program can increase sports performance by obtaining a better rank in specific races. (2) Methods: Seven male mountain runners with good results at the international level participated in the research, which featured an initial and a final test. The initial test took place in March at the beginning of the competitive season, and the final test took place in September at the end of the annual training plan in 2021. The entire experiment used invasive tests, such as taking blood samples to perform blood biochemistry analysis, and non-invasive tests, such as mountain running races, determinations of VO2max, EKGs, urine biochemistry and NeuroTracker tests. (3) Results: Comparing the initial test with the final one from a statistical point of view, a significant improvement was found in the final test regarding the obtained results in most tests and, most importantly, the occupied position in the final general rank (p = 0.005). The main variations after effort were decreased Ca++ and increased Cl−, a low TGL level if the diet was inadequate, increased LDH and CPK strongly correlated with the skeletal muscle response, and only physiological changes were found in the EKG and urine summary. (4) Conclusions: The invasive and non-invasive tests applied in this study provided crucial information on the athletes’ health statuses, enabling the coach to adjust the training program in light of the findings in order to improve sports performance and avoid overexertion.
Keywords: performance; technology; prevention; VO2max; NeuroTracker